Individual variation in the cortisol response to a simulated Olympic weightlifting competition is related to changes in future competitive performance - Blair T Crewther; Christian Cook; Joanna Orysiak; Piotr Zmijewski; Zbigniew Obmiński (Termedia Publishing House, 2019)
The cortisol (C) and testosterone (T) responses to experimental stress have been linked to sport and health outcomes several days to years later. Here we examined the utility of these biomarkers, taken across a simulated Olympic weightlifting (OWL) competition, as predictors of future competitive performance in young athletes. Seventy junior athletes (46 males, 24 females) participated in a talent identification and development programme that replicated an OWL competition. Performance was indexed by the total load lifted, relative to body mass, with serum changes in C (∆C) and (∆T) concentrations profiled. We identified each athlete's best performance in real competitions over two subsequent years via online resources. Hierarchical regression was used to predict changes in competitive performance at